2018
DOI: 10.1111/jocd.12790
|View full text |Cite
|
Sign up to set email alerts
|

Appearance‐based vs health‐based sun protective messages: A randomized, double‐blind controlled study

Abstract: Summary Background Appearance‐based messages have shown promise in improving sun protection habits among Caucasians but have scarcely been investigated in Hispanic populations. Objective To compare the effectiveness of appearance‐based vs health‐based messages in an ethnic patient population, where hyperpigmentation disorders are prevalent and often cosmetically concerning. Methods One hundred thirty‐seven patients were randomized to receive images of (a) skin cancer, (b) hyperpigmentation, or (c) wrinkles. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…11,[19][20][21] Some recent studies have shown that young people are more prone to protect themselves from the sun due to the increasing cosmetic concerns and preventing photoaging. [22][23][24][25] Sunscreen use is higher among women, people with a higher education level and younger than 65 years, but paradoxically sunbathing/tanning habits were also found higher in women. 11 In a recent study about the relation between the primary spoken language (native or non-native) and the sun-related behaviors in adults with sun exacerbated dermatoses, it was reported that those who used sunscreen and had higher level of education were more likely to know their illness when compared to patients who did not.…”
Section: Discussionmentioning
confidence: 99%
“…11,[19][20][21] Some recent studies have shown that young people are more prone to protect themselves from the sun due to the increasing cosmetic concerns and preventing photoaging. [22][23][24][25] Sunscreen use is higher among women, people with a higher education level and younger than 65 years, but paradoxically sunbathing/tanning habits were also found higher in women. 11 In a recent study about the relation between the primary spoken language (native or non-native) and the sun-related behaviors in adults with sun exacerbated dermatoses, it was reported that those who used sunscreen and had higher level of education were more likely to know their illness when compared to patients who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians, scientists, and health care workers should form alliances with technology companies to develop creative ways to use social media to influence people with the right messages. It is crucial to develop messages that shift norms about ideals of appearance around a more healthy appearance rather than merely a beautiful appearance [ 40 ]. It is also important to consider the content of these messages; image-based messages appear to be more effective for skin cancer prevention [ 41 ].…”
Section: Final Remarksmentioning
confidence: 99%
“…Our identification of strategies for reaching a greater audience within Instagram is made even more important by De La Garza et al’s conclusion that Instagram can have a strong impact on users’ sun‐protective behaviors, 3 and Cheng et al's finding that young female Instagram users have been shown to exhibit indoor tanning behaviors, demonstrating a need for sun protection education within this population 3,4 …”
mentioning
confidence: 99%
“…photo posts can only be accessed by the public depending on the user's permission settings.Our identification of strategies for reaching a greater audience within Instagram is made even more important by De La Garza et al's conclusion that Instagram can have a strong impact on users' sun-protective behaviors,3 and Cheng et al's finding that young female Instagram users have been shown to exhibit indoor tanning behaviors, demonstrating a need for sun protection education within this population 3,4. Further substantiating the need for dermatologist representation on Instagram is social media's ability to quickly disseminate false information 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation